The impact of IoT and 3D printing on job quality and work organisation: A snapshot from Spain - Rafael Grande; Alberto Vallejo-Pe\~na; Cesira Urzi Brancati (European Commission, Joint Research Centre (JRC), 2021)
This paper analyses how the introduction of advanced digital technologies affected the business model, work organisation, and job quality in selected establishments in Spain. The focus is on two technologies: 3D printing and Internet of things (IoT). Two case studies were carried out in Spain: TTI-Algeciras (stowage and logistic port container terminal) and Airbus (manufacture of aerospace and defence equipment). A qualitative research methodology through semi-structured interviews was implemented. The results show the selected digital technologies has a positive impact on the busi-ness model of TTI-Algeciras and Airbus, either by increasing efficiency and competitiveness, or by improving work organisation. The main findings in terms of job quality, are: improvements in the physical environment resulting from a reduction in occupational hazards: the upskilling of the work-force, due to the need of new technical skills; the increase in worker responsibility and autonomy to the detriment of routine tasks; and, on the negative side, an intensification of work that is now de-termined by the technology. The analysis also shows the importance of communication and new ways of organising teamwork as a crucial factor for the successful introduction of digital technolo-gies in both companies. Finally, the consequences of the restrictive measures against Covid-19 during 2020 have favoured an acceleration of technological change in the workplace.
Keywords: 330; 3D printing; Internet of Things (IoT); digitisation; digitalisation; digital technologies; future of work